SARS-CoV-2 in first trimester pregnancy: a cohort study - Nina la Cour Freiesleben; Pia Egerup; Kathrine Vauvert Römmelmayer Hviid; Elin Rosenbek Severinsen; Astrid Marie Kolte; David Westergaard; Line Olsen; Lisbeth Prætorius; Anne Zedeler; A.-M. H. Christiansen; Josefine Reinhardt Nielsen; Didi Bang; et al. (2020)
STUDY QUESTION: Does maternal infection with SARS-CoV-2 in first trimester pregnancy have an impact on the fetal development as measured by nuchal translucency thickness and pregnancy loss? SUMMARY ANSWER: Nuchal translucency thickness at the first trimester scan was not significantly different in pregnant women with versus without SARS-CoV-2 infection in early pregnancy and there was no significant increased risk of pregnancy loss in women with SARS-CoV-2 infection in the first trimester. WHAT IS KNOWN ALREADY: Pregnant women are more vulnerable to viral infections. Previous coronavirus epidemics have been associated with increased maternal morbidity, mortality and adverse obstetric outcomes. Currently, no evidence exists regarding possible effects of SARS-CoV-2 in first trimester pregnancies. STUDY DESIGN, SIZE, DURATION: Cohort study of 1,019 women with a double test taken between Feb. 17 and Apr. 23, 2020, as a part of the combined first trimester risk assessment, and 36 women with a first trimester pregnancy loss between Apr. 14 and May 21, 2020, prior to the double test. The study period was during the first SARS-CoV-2 epidemic wave in Denmark. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cohort 1 included pregnant women with a double test taken within the study period. The excess serum from each double test was analyzed for SARS-CoV-2 antibodies. Results were correlated to the nuchal translucency thickness and the number of pregnancy losses before or at the time of the first trimester scan. Cohort 2 included women with a pregnancy loss before the gestational age for double test sample. Serum from a blood test taken the day the pregnancy loss was identified was analyzed for SARS-CoV-2 antibodies. The study was conducted at a public university hospital serving approximately 12% of pregnant women and births in Denmark. All participants in the study provided written informed consent. MAIN RESULTS AND THE ROLE OF CHANCE: Eighteen (1.8%) women had SARS-CoV-2 antibodies in the serum from the double test suggestive of SARS-CoV-2 infection in early pregnancy. There was no significant difference in nuchal translucency thickness for women testing positive for previous SARS-CoV-2 infection (n = 18) versus negative (n = 994) (p = 0.62). There was no significant increased risk of pregnancy loss for women with positive antibodies (n = 1) (OR 3.4, 0.08-24.3 95% CI, p = 0.27). None of the women had been hospitalized due to SARS-CoV-2 infection. None of the women with pregnancy loss prior to the double test (Cohort 2) had SARS-CoV-2 antibodies. LIMITATIONS, REASONS FOR CAUTION: These results may only apply to similar populations and to patients who do not require hospitalization due to SARS-CoV-2 infection. A limitation of the study is that only 1.8% of the study population had SARS-CoV-2 antibodies suggestive of previous infection. WIDER IMPLICATION OF THE FINDINGS: Maternal SARS-CoV-2 infection had no effect on the nuchal translucency thickness and there was no significant increased risk of pregnancy loss for women with SARS-CoV-2 infection in first trimester pregnancy. Evidence concerning Covid-19 in pregnancy is still limited. These data indicate that infection with SARS-CoV-2 in not hospitalized women does not pose a significant threat in first trimester pregnancies. Follow up studies are needed to establish any risk to a fetus exposed to maternal SARS-CoV-2 infection. STUDY FUNDING/COMPETING INTEREST(S): Prof. Henriette Svarre Nielsen (HSN) and colleagues received a grant from the Danish Government for research of Covid-19 among pregnant women. The Danish government was not involved in the study design, data collection, analysis, interpretation of data, writing of the report or decision to submit the paper for publication. AI, JOL, JBR, DMS, JEF, and ERH received funding from a Novo Nordisk Foundation (NNF) Young Investigator Grant (NNF15OC0016662) and a Danish National Science Foundation Center Grant (6110-00344B). AI received a Novo Scholarship. JOL is funded by an NNF Pregraduate Fellowship (NNF19OC0058982). DW is funded by the NNF (NNF18SA0034956, NNF14CC0001, NNF17OC0027594). AMK is funded by a grant from the Rigshospitalet's research fund. Henriette Svarre Nielsen has received speakeŕs fees from Ferring Pharmaceuticals, Merck Denmark A/S and Ibsa Nordic (outside the submitted work). Nina la Cour Freiesleben has received a grant from Gedeon Richter (outside the submitted work). Astrid Marie Kolte has received speakeŕs from Merck (outside the submitted work). The other authors did not report any potential conflicts of interest.